Context Drives Diversification of Monocytes and Neutrophils in Orchestrating the Tumor Microenvironment - Jeong, Juhee; Suh, Yoorock; Jung, Keehoon (Frontiers in Immunology, 2019)
Recent preclinical/clinical studies have underscored the significant impact of tumor microenvironment (TME) on tumor progression in diverse scenarios. Highly heterogeneous and complex, the tumor microenvironment is composed of malignant cancer cells and nonmalignant cells including endothelial cells, fibroblasts, and diverse immune cells. Since immune compartments play pivotal roles in regulating tumor progression via various mechanisms, understanding of their multifaceted functions is crucial to developing effective cancer therapies. While roles of lymphoid cells in tumors have been systematically studied for a long time, the complex functions of myeloid cells have been relatively underexplored. However, constant findings on tumor-associated myeloid cells are drawing attention, highlighting the primary effects of innate immune cells such as monocytes and neutrophils in disease progression. This review focuses on hitherto identified contextual developments and functions of monocytes and neutrophils with a special interest in solid tumors. Moreover, ongoing clinical applications are discussed at the end of the review.